In a recursively defined arithmetic sequence, the common difference can be determined from the recursive formula.
In your case, the sequence is defined as:
- \( a_1 = 4 \)
- \( a_n = a_{n-1} - 5 \)
The common difference \( d \) is the amount that each term differs from the previous term. From the recursive definition \( a_n = a_{n-1} - 5 \), we can see that each term is obtained by subtracting 5 from the previous term.
Therefore, the common difference is: \[ d = -5 \]
So, the common difference is \( -5 \).